Keragaman dan Pemanfaatan Simplisia Nabati yang Diperdagangkan di Purwokerto - Mei Utami; Yayu Widiawati; Hexa Apriliana Hidayah (Fakultas Biologi | Universitas Jenderal Soedirman, 2013)
A study to know the kinds of plant simplicia sold in Purwokerto and their usage as traditional medicine. A survey and sampling of simplicia plant has been conducted in Purwokerto. An interview has also been done carried out for different respondants. The data recorded included simplicia type their local names, their pictures and classification, simplicia parts and their uses. The result of this research showed that there are 50 types of simplicia included in 26 families used as traditional medicines in Purwokerto. The simplicia is used by boiling in a container made of clay soil, fried, poured by oil water, or cooked. Parts that are used as simplicia comprised are rhizome, leave, stem, bark, thallus, fruit, fruit peel, flower, herbals (root, stem and leaves) and seeds. The uses of simplicia included carminative (remove stomach gas), anti inflammation, analgesic (pain healing), anti pyretic (heat lowering) cholagogum (making fluency of bile into duodenum), stomachic (increase appetite), anti spasmodic, choleritic (increase bile juice production), antelminthic (eradicate worm), sliming and tonic (body freshener).